Global Existence and Asymptotic Stability for the Initial Boundary Value Problem of the Linear Bresse System with a Time-Varying Delay Term (Journal of Partial Differential Equations, 2019)
The authors of this paper study the Bresse system in bounded domain withdelay terms. First, we prove the global existence of its solutions in Sobolev spaces bymeans of semigroup theory. Furthermore, the asymptotic stability is given by using anappropriate Lyapunov functional.
Keywords: Semi group approach; Bresse system; energy decay.